Adaptive Control of Quadruped Locomotion Through Variable Compliance of Revolute Spiral Feet. (9th October 2014) - Mutka, Alan; Kočo, Edin; Kovačić, Zdenko
In this article we present a novel mechanical design of a robot leg that possesses active and variable passive compliance properties. The hip and knee joints provide active compliance, while the variable passive compliance comes from the spiral foot spring, mounted on the ankle joint, which changes its stiffness by rotating and changing contact angle with the ground. The stiffness of the foot for various contact angles was identified experimentally by using the strength tester measurement system. The method for damping coefficient identification, based on the observation of energy losses during the stance phase of leg hopping motion, is described and used to obtain the foot damping model. The adaptation of spiral foot stiffness to varying ground stiffness is achieved by extracting a leg contact time from a feedback signal provided by a flex sensor mounted on the foot. The experiments on a single leg and quadruped platforms have confirmed that the presented spiral foot design provides stiffness adaptability, partial recovery of the energy from the previous hop and restriction of stance contact time, which are all necessary conditions to obtain more efficient quadruped locomotion.